Reality-Illusion of the Climate Policy of Germany - Rupert Pritzl (Wirtschaftsdienst)
Abstract Climate protection is a huge global challenge and climate policy can be characterised as an international public good problem. The climate policy of Germany is limited, expensive and inefficient and does not contribute to the desired reduction of the CO2-emissions. But why? Why are we in Germany subject to an illusion of climate policy? There are multiple reasons: Politicians seem unwilling to sufficiently learn and appear unable to concede they are wrong. Politics get entangeld in distributional conflicts with EEG lobby groups and orchestrate their pretend efforts in public. Politicians tend more to dirigistic than to market-based policy instruments and ease the urge towards distributional interventions in the market. These findings will be analysed in the light of the New Institutional Economics.